K-State Research and Extension 2019 Annual Report - Minton, Ernest J. (My University, 2019)
This informal report to the Kansas Legislature summarizes the wide-ranging impact of K-State Research and Extension in 2019, highlighting initiatives in agriculture, environmental stewardship, public health, and community development across Kansas.
UNN34B_2019_01
Keywords: UNN34B; Administrative and Research Reports; legislature